Variation in Mesopic Retinal Sensitivity Relative to Distance from Geographic Atrophy in Age-Related Macular Degeneration - Souvick Mukherjee, PhD; Emily Vance, MPH; Leon von der Emde, MD; Thilaka Arunachalam, BS; Tharindu De Silva, PhD; Alisa T. Thavikulwat, MD; Christine Orndahl, PhD; Caroline Nyaiburi, MS; Maria Abraham, ScM; Keri Hammel, MS; SriniVas R. Sadda, MD; Emily Y. Chew, MD; et al. (Ophthalmology Science)
Purpose: To analyze the relationship between distance from geographic atrophy (GA) lesion borders and mesopic retinal sensitivity in age-related macular degeneration (AMD). Design: Exploratory analyses of the longitudinal microperimetry dataset from a recent phase II, prospective, single-arm, nonrandomized trial of oral minocycline for GA progression. Participants: Individuals with GA from AMD in ≥1 eye. Methods: Mesopic retinal sensitivity was assessed longitudinally with a fundus-guided microperimetry device at baseline, month 3, and every 6 months thereafter, using a custom T-shaped test pattern centered on the fovea. Individual test loci were superimposed on an aligned fundus autofluorescence image and distance from the closest GA lesion border (GA distance) was computed. The relationship between GA distance and retinal sensitivity was analyzed in study eyes using repeated-measures regression. Main Outcome Measures: Mesopic retinal sensitivity. Results: The study population comprised 26 study eyes from 26 participants (mean age 74.2 years). Retinal sensitivity of extralesional testing loci increased steeply, as a quadratic function, between 0° and 2.05° (i.e., knot at 2.05°; 95% confidence interval [CI] 1.26°–2.84°) of GA distance. Beyond 2.05°, it increased linearly and less steeply. In nonlinear analyses accounting for nesting, a significant effect of GA distance on retinal sensitivity was observed. For GA distances <2.05°, sensitivity increased quadratically by approximately 1.99 decibels (dB)/° (95% CI: 1.15, 2.83 dB/°; P < 0.001) or higher. For GA distances ≥2.05°, sensitivity increased at 0.56 dB/° (95% CI: 0.42, 0.70 dB/°; P < 0.001). There was also a significant effect of time on sensitivity (estimate: −0.07 dB/month; 95% CI: −0.08, −0.06 dB/month; P < 0.001). Conclusions: The results demonstrate a perilesional zone 2° (∼580 μm) around the GA border in which retinal sensitivity changes steeply according to GA distance. This zone presents an important focus for closer evaluation in interventional studies examining potential efficacy for the preservation or recovery of retinal function. With GA progression, decreased retinal sensitivity expands ahead of GA expansion itself, as an advancing wave. Overall, the degree and extent of decreased visual function beyond GA borders have important implications for the design of clinical trials, decision-making in clinical practice, and insights into AMD pathophysiology. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.